Analisis Nilai Moral dalam Cerita Rakyat Sultan Hadlirin dan Masjid At-Taqwa Loram Kulon Kudus - Fitmaya Intan Nazwa; Lu’luul Maknun; Muhammad Zaki Ali; Mohammad Kanzunnudin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Folklore is an oral cultural heritage that contains moral values and local wisdom that are important to be transmitted to the younger generation. This study aims to identify and describe the moral values in the folklore "Sultan Hadlirin and At-Taqwa Mosque Loram Kulon Kudus" contained in the book Cerita Rakyat Pesisir Timur by Mohammad Kanzunnudin. The method used is descriptive qualitative with data collection techniques in the form of observing and taking notes and data analysis using the Miles and Huberman model (data reduction, data presentation, and drawing conclusions). The results of the study indicate that this story contains a number of main moral values, namely responsibility, religiosity, social concern, and tolerance. This finding confirms that folklore is not only a medium of entertainment and cultural preservation, but also a means of character education that is relevant to answer the moral challenges of today's young generation. Therefore, the integration of folklore in moral education needs to be encouraged in order to strengthen cultural identity and form individuals with noble character.